One piece. Vol. 1, Romance dawn - Oda, Eiichiro, 1975-; Caselman, Lance; Nakatani, Andy (San Francisco, CA : Viz, 2003)
Vowing to become the king of the pirates, Luffy sets out in a rowboat in search of the legendary "One Piece", which is said to be the greatest treasure in the world.
"This book reads from right to left"--Cover p. [4].
"This graphic novel contains material that was originally published in English in Shonen Jump #1-4 plus the first One piece episode in Shonen Jump #5"--P. facing t.p.
Translated from the Japanese.
Adult
Keywords: Pirates -- Fiction; Treasure troves -- Fiction; Buried treasure -- Fiction; Comic books, strips, etc; Pirates -- Fiction; Adventure fiction; Graphic novels